(untitled) (Bioresearch Communications, 2021)
To minimize the outspread of COVID-19, the government announced the closure of all educational institutions on March 18, 2020, and it has continued since then. This extended break from educational institutes has affected the lives of students profoundly. Though face-to-face classes have been replaced by online classes, the effectiveness of the online learning system is impeded by poor technological infrastructure and stable internet access. Besides, important exams like board exams, university admission exams, and university semester exams have been suspended during this period resulting in session jam. Numerous students are also going through learning loss. Apart from academic loss, there have been reported augmented cases of child marriage, child labor, child abuse, malnutrition, and online abuse due to the extended shutdown. This protracted closure has also impacted students’ mental health, physical activity, and behavioral changes. Hence, there have been increased incidences of depression, mental disorders, and suicides. Considering all these aspects, now both parents and students intend to recommence the in-person classes supporting the reopening of all institutes. Bioresearch Commu. 7(2): 1038-1041, 2021 (June)